Exploring the Macroscopic and Microscopic Characteristics of Acalypha indica L. Simplisia Powder in the Context of Pharmabotanical Studies - Saristiana, Yuneka; Anita Dwi Setyarini; Yunita Dian Permatasari; Hasriyani; Arikha Ayu Susilowati; Fendy Prasetyawan (International Journal of Contemporary Sciences (IJCS), 2024)
Botanical studies form a cornerstone in pharmacy, providing insights into the therapeutic potential of medicinal plants. Acalypha indica L., commonly known as "Anting-anting," holds a significant place in traditional medicine. This research focuses on the macroscopic and microscopic analysis of Acalypha indica L. simplisia, aiming to contribute to its pharmacognostic profile and enhance the standardization of herbal formulations. The exploration encompasses its historical context, traditional uses, chemical constituents, and in vitro anti-arthritis activity. The study employs advanced tools, including optical and electron microscopes, for a comprehensive examination. The macroscopic analysis involves meticulous observation of external features, while the microscopic examination delves into cellular and tissue structures. This research aligns with contemporary pharmacognosy, bridging traditional knowledge with scientific approaches, fostering a deeper understanding of medicinal plant potential